Ferroelectricity of Dion–Jacobsen layered perovskites CsNdNb2O7 and RbNdNb2O7. (27th August 2020) - Asaki, Sota; Akamatsu, Hirofumi; Hasegawa, George; Abe, Tomohiro; Nakahira, Yuki; Yoshida, Suguru; Moriyoshi, Chikako; Hayashi, Katsuro
Abstract: Crystallography and dielectric properties in Dion–Jacobson layered perovskites, CsNdNb2 O7 and RbNdNb2 O7, have been examined in dense polycrystalline samples, and polarization hysteresis loops that substantiate ferroelectricity have been observed at room temperature. The theoretical mechanism for the spontaneous polarization, "hybrid improper ferroelectric mechanism, " induced by a combination of two types of non-polar octahedral rotations, is confirmed in these two phases. Our samples show remanent polarizations of 2–3 μ C cm −2, which are much larger than those obtained in polycrystalline samples with the hybrid improper ferroelectricity reported so far. A dielectric constant in CsNdNb2 O7 exhibits an anomaly at 625 K, corresponding to the ferroelectric transition, as previously revealed by X-ray and neutron diffractometry. No dielectric anomaly is observed for RbNdNb2 O7 throughout the temperature range studied here (≤773 K), which is consistent with the previous diffractometry showing the persistence of polar I2 cm symmetry up to 790 K.